Analysis of Data Mining Application in Receiving Students of Lhokseumawe Polytechnic Students Using K-Means Algorithm - Desita Ria Yusian TB; Hayatun Maghfirah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Utilization of information technology in the process of acceptance. Data mining is the excavation of new information by searching for certain patterns or rules of large amounts of data expected to overcome the condition. By utilizing the registration data and passing test data is expected to produce information pengcllusteran and interrelationship relationship between the Department with the Student Entry Path. The algorithm used in this research is K-Means algorithm, The algorithm is arranged on the basis of a simple idea. Information generated by student data filtering graphs, graph with percentage of input path 323.0 and invitation path 105.0 seen in Electrical Engineering department.Keywords: Data Mining, K-Means, Departments and Entrance Line, Cluster